The Chevalier d'Auriac - Levett Yeats, S. (Sidney), 1858?-1916 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Chevalier d'Auriac" by S. Levett Yeats is a historical novel written in the late 19th century. It follows the complex life and adventures of Alban de Breuil, the Chevalier d'Auriac, set against the backdrop of the turbulent political landscape of France during the Wars of Religion. The narrative begins with Alban embroiled in the tensions of the ongoing conflicts, navigating personal rivalries, love, and the broader questions of loyalty and honor amidst war. The opening of the book immerses the reader in a tense scene where d'Auriac and his rival, de Gomeron, engage in a game of chance that soon turns hostile. In the midst of their conflict, they are interrupted by the arrival of prisoners, a man and a woman, who are suspected spies. The beautiful woman$1 (Bs courageous plea for mercy captivates the soldiers and incites dramatic actions that set the stage for d'Auriac's character development and his evolving motivations. As the story unfolds, themes of bravery, honor, and the challenges of warfare emerge, underscoring the protagonist's journey through both battle and personal turmoil. (This is an automatically generated summary.)s
Release date is 2011-12-17
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: Adventure stories; France -- History -- Henry IV, 1589-1610 -- Fiction